Financial Literacy and Use of Financial Technology Payment for Consumptive Behavior - Ade Gunawan (Fakultas Ekonomi dan Bisnis, Universitas Muhammadiyah Sumatera Utara, 2023)
The low knowledge of students' financial literacy so that they do not have awareness in managing finances which makes students behave consumptively, so the purpose of this study was to determine the effect of financial literacy and the use of financial technology payments on consumptive behavior of students at the Faculty of Economics and Business, Muhammadiyah University of North Sumatra. The approach used in this research is a quantitative research approach and uses primary data, the sample in this study is 100 respondents using quota sampling technique. The data analysis technique used is Structural Equation Modeling (SEM) Part Least Square (PLS). The results of the study show that financial literacy and financial technology payments have a significant effect on consumptive behavior among students of the Faculty of Economics and Business, Universitas Muhammadiyah Sumatera Utara.